2013
DOI: 10.1140/epjst/e2013-01857-4
|View full text |Cite
|
Sign up to set email alerts
|

Ordinal pattern statistics for the assessment of heart rate variability

Abstract: Abstract. The recognition of all main features of a healthy heart rhythm (the so-called sinus rhythm) is still one of the biggest challenges in contemporary cardiology. Recently the interesting physiological phenomenon of heart rate asymmetry has been observed. This phenomenon is related to unbalanced contributions of heart rate decelerations and accelerations to heart rate variability. In this paper we apply methods based on the concept of ordinal pattern to the analysis of electrocardiograms (inter-peak inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 20 publications
2
30
0
Order By: Relevance
“…There was an increase in the percentage of acceleration and deceleration runs, which caused the decrease of PermEn values concerning the NEG_CB group (Table 3). In our previous work, we analyzed the distribution of patterns in 97 healthy volunteers and concluded that acceleration and deceleration runs seem to be mostly related to sympathetic influences [41]. In fact, this supports our hypothesis that in patients with vasovagal faints, high baseline sympathetic modulation prevents the incidence of syncope during the head-up tilt.…”
Section: Neg Vs Vvs_2 Groupssupporting
confidence: 76%
“…There was an increase in the percentage of acceleration and deceleration runs, which caused the decrease of PermEn values concerning the NEG_CB group (Table 3). In our previous work, we analyzed the distribution of patterns in 97 healthy volunteers and concluded that acceleration and deceleration runs seem to be mostly related to sympathetic influences [41]. In fact, this supports our hypothesis that in patients with vasovagal faints, high baseline sympathetic modulation prevents the incidence of syncope during the head-up tilt.…”
Section: Neg Vs Vvs_2 Groupssupporting
confidence: 76%
“…It allows to classify different types of behaviors [20,21], to detect dynamical changes [22][23][24], etc. (see [25,26] for many examples).…”
Section: Introductionmentioning
confidence: 99%
“…There are moreover symmetries in the ordinal pattern distributions related to time and data range reversal. Both can be exploited when considering special orderrelated aspects of data analysis; for example, for describing roughness by change statistics [86] and for quantifying the phenomenon of heart rate asymmetry [40] described above. 3.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, frequencies of single ordinal patterns are of some interest. For example, Graff et al [40] have discussed the recently found physiological phenomenon of heart rate asymmetry on the basis of ordinal pattern frequencies, providing new views on this topic. In particular, they present a study which shows significant frequency differences for some ordinal 4-patterns and their time reversals in the heart rate data of healthy subjects.…”
Section: Ordinal Pattern Distributions Of Empirical Data (A) Ordinal mentioning
confidence: 99%